Procedures for Translating Coinages in Children’s Literature into Malay - Zabir, Atikah (Forum for Linguistic Studies, 2025)
Vocabulary acquisition is a key part of reading, especially for child readers. Additionally, as part of the child development and language acquisition process, children experiment with the articulation of sounds and words. Hence, children’s literature often contains lexical creativity, such as coinages. Due to the nature of the formation, coinages are deeply rooted in the structure of the language they were built in. It is also important to note that authors often compress information, and thus meanings, through new words. The complexity of coinages means translators must consider various factors when translating this element. Therefore, this study will identify coinages in children’s literature and analyse the procedures used to translate this element from English into Malay. The results of the study show that coinages can occur not only as a new word with a new meaning (morphosemantic coinage) but also as an existing word with a new meaning (semantic coinage), as well as a new form that retains the original meaning (morphological coinage). There is no one correct way to deal with coinages in translation, as this study has found. Translators’ choices also reflect their conscious decisions related to the form and function of the coined items